Effects of continuous and repeated dry heat treatment on the technological properties of green banana (Musa paradisiaca) starch - RUTHS, Luana Carolina; MAIOR, Luane de Oliveira; BACH, Daniele; ROMKO, Stéphanie Schiavo; SCHNITZLER, Egon; DEMIATE, Ivo Mottin; Lacerda, Luiz Gustavo (Food Science and Technology, 2024)
Starch is an important ingredient used in numerous industrial applications. The utilization of nonconventional sources of this carbohydrate enables the improvement of functional properties and reduces waste from certain botanical sources such as green bananas. This study aimed to evaluate the effects of dry heat modification with varying cycles (1–3) and times (3–9 h) on the thermal, paste, structural, and morphological properties, and digestibility of green banana starch, comparing them with native starch. The gelatinization enthalpy decreased with the applied treatment, especially for starches treated with repeated cycles. The peak viscosity, as observed in the RVA curve, decreased after treatment. X-ray diffractometry remained unchanged, while relative crystallinity decreased. The morphology exhibited slight alterations after the treatment. The slow digestibility of the treated starches showed a significant increase compared to the digestibility of native starch.